2012
DOI: 10.1111/j.1468-2494.2012.00746.x
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to acute electromagnetic radiation of mobile phone exposure range alters transiently skin homeostasis of a model of pigmented reconstructed epidermis

Abstract: Exposure to electromagnetic radiations (EMR) produced by mobile phone concerns half the world's population and raises the problem of their impact on human health. In this study, we looked at the effects of mobile phone exposure (GSM basic, 900 MHz, SAR 2 mW g(-1) , 6 h) on a model of pigmented skin. We have analysed the expression and localization of various markers of keratinocyte and melanocyte differentiation 2, 6, 18 and 24 h after EMR exposure of reconstructed epidermis containing either only keratinocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…These findings were obtained by testing three signal types (CW, GSM basic and GSM talk) and by employing several tests to measure apoptosis. Simon et al (2013), exposed reconstruct epidermis from human skin biopsy to 900 MHz, GSM basic for 6 h at an SAR level of 2 W/kg. After RF exposure, growth medium was replaced with fresh medium, and reconstructed epidermis was incubated at 37 °C and 5% CO2 for 2, 6, 18 or 24 h. Results indicated no significant variation of p53 and caspase 3 in exposed samples compared to sham exposed ones.…”
Section: Non Genotoxic Effectsmentioning
confidence: 99%
“…These findings were obtained by testing three signal types (CW, GSM basic and GSM talk) and by employing several tests to measure apoptosis. Simon et al (2013), exposed reconstruct epidermis from human skin biopsy to 900 MHz, GSM basic for 6 h at an SAR level of 2 W/kg. After RF exposure, growth medium was replaced with fresh medium, and reconstructed epidermis was incubated at 37 °C and 5% CO2 for 2, 6, 18 or 24 h. Results indicated no significant variation of p53 and caspase 3 in exposed samples compared to sham exposed ones.…”
Section: Non Genotoxic Effectsmentioning
confidence: 99%
“…But, some investigator reported that the electromagnetic radiation (900 MHz, SAR 2 mWg -1 ) did not affect to skin at the point of cellular stress and pigmentation [10]. But electromagnetic radiation and electromagnetic field are different physical area, therefore, the results of each stimulations could not the same.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that non-thermal effects of EMR could induce lipid peroxidation in human erythrocytes [ 7 ], oxidative damage in rabbits and rat’s brains [ 8 , 9 , 10 ], and alteration of epidermal homeostasis [ 11 ]. EMR exposure may also induce changes in the endocrine system [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%